2020
DOI: 10.1590/0102-311x00090619
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with food-related life and life satisfaction: a triadic analysis in dual-earner families

Abstract: This study explored the spillover and crossover associations between satisfaction with food-related life and life satisfaction in mothers, fathers and adolescent children in dual-earned families. This is a cross-sectional design study with mothers, fathers and children surveyed in Temuco, Chile. The participants were 303 dual-earner parents and their adolescent children (mean age 13.3 years, 51.5% female). Actor-partner Interdependence Model (APIM) and structural equation modeling were used to explore spillove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 44 publications
1
16
3
Order By: Relevance
“…Nevertheless, other studies show that men’s satisfaction can also be influenced by their female partners [ 25 , 34 ]. In addition, when the relationship between one related variable among couples and their satisfaction with life, as well as satisfaction with different domains of life, are measured at the same time, symmetric crossover effects have been reported for some outcomes and asymmetric crossover effects for others [ 34 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, other studies show that men’s satisfaction can also be influenced by their female partners [ 25 , 34 ]. In addition, when the relationship between one related variable among couples and their satisfaction with life, as well as satisfaction with different domains of life, are measured at the same time, symmetric crossover effects have been reported for some outcomes and asymmetric crossover effects for others [ 34 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Cheung [ 25 ] found that work-to-family enrichment in women was positively associated with their husbands’ life satisfaction but not vice versa. Schnettler et al [ 38 ] found that in men, work-life balance was positively associated with their own satisfaction with life as well as with their female partner’s life satisfaction; in women, however, their work-life balance was positively associated with their own satisfaction with life, but not with that of their male partner.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations